PELATIHAN LABELING DAN PACKAGING BAGI PELAKU UMKM DI DESA CIHERANG KECAMATAN GUNUNG SARI, KABUPATEN SERANG - Surti Zahra; Bagaskara Aditya Pratama; Diana Diana; Aditya Sri Novita; Astin Mandela Puspa (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The community of Ciherang village, Gunung Sari sub-district, several housewives to improve their family's economy carry out entrepreneurial activities. There are various kinds of entrepreneurial activities depending on the expertise/ability of each individual. One of the UMKM  in Ciherang Village is Baso aci or commonly called boci. These aci meatballs are pure meatballs made from starch dough without being mixed with ground beef. From the main ingredient of starch, or Sundanese people call it aci, it looks similar to the cilok sauce that we often encounter. The problem that was encountered after we conducted the survey was the lack of handling of packaging or packaging on the baso aci, therefore the solution we gave was to increase UMKM in Ciherang village. as well as additional menus to complement these UMKM products to make them more attractive and in demand by consumers by holding labeling and packaging training for UMKM baso aci players in Ciherang Village